Two Rediscoveries of the Autostereogram in the 1960s. (February 2020) - Sawada, Tadamasa; Rozhkova, Galina I.
The autostereogram (ASG) was discovered in the 1840s and again in the 1960s. It is acknowledged that Pete Stephens rediscovered the ASG serendipitously when he constructed an image with a repetitive pattern manually in the late 1960s. But, the principle and application of the ASG were described by Lev Mogilev from Irkutsk State University earlier in the 1960s.